Atividade Citotóxica da Viridicatum toxina A obtida de Penicillium sp. e sua Potencialidade no Tratamento de células Tumorais Humanas - Emylli Areco Pereira (2023)
Viridicatum toxins (VTs) are substances produced by endophytic fungi of various species of the Penicillium, Aspergillus, and Paecilomyces family. Recognized for its antimicrobial actions, it is considered a potent antibiotic belonging to the tetracycline family; both have a tetracyclic carboxamide nucleus in their composition. In addition to this antibiotic activity, Viridicatum toxin A (VTA) and its analogues, Viridicatum toxin B, C, D, E, F, spirohexalin and previridicatumtoxin, have shown in previous studies, promising results of cytotoxicity in neoplastic cells of lung, colon and cervixus in vitro. In this study, experiments were performed to verify the cytotoxicity of Viridicatum toxin A, using the monolayer cell culture model. Breast (MCF7), triple-negative breast (MDA-MB-231), kidney (786-0), liver (HepG2) and colon (HT29) cancer lines were treated at concentrations of 0.1, 1, 10 and 100 µg/mL and showed GI50 results between 6.13 and 16.12 µg/mL, with selectivity for all of them at the concentration of 10 µg/mL. Subsequently, two strains of interest, 786-0 and MDA-MB-231 were tested with acridine orange and ethidium bromide, at concentrations of GI50 and 2x GI50, which were very close to the selective concentration, in order to verify cell viability, where both strains showed morphological changes that indicated presence of cell death by apoptosis pathway. This is reinforced, mainly, by previous studies involving Viridicatum toxin A, which demonstrated the induction of apoptosis in cervical cancer cells (HeLa), through the arrest of the G2/M pathway; moreover, in triple-negative breast lineage, tetracyclines, which are structurally similar to VTs, induced apoptosis through the inhibition of MMPs (matrix metalloproteinases). Thus, we conclude that ATV is a substance with potential as an antitumor agent for presenting potent antiproliferative and cytotoxic activity, selective at the concentration of 10 µg/mL and with indications of stimulating cell injury by the apoptosis cell death pathway.